2017
DOI: 10.1155/2017/4101735
|View full text |Cite
|
Sign up to set email alerts
|

Hazardous Effects of Titanium Dioxide Nanoparticles in Ecosystem

Abstract: Although nanoparticles (NPs) have made incredible progress in the field of nanotechnology and biomedical research and their applications are demanded throughout industrial world particularly over the past decades, little is known about the fate of nanoparticles in ecosystem. Concerning the biosafety of nanotechnology, nanotoxicity is going to be the second most priority of nanotechnology that needs to be properly addressed. This review covers the chemical as well as the biological concerns about nanoparticles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(59 citation statements)
references
References 89 publications
(149 reference statements)
1
48
1
Order By: Relevance
“…lipid peroxidation), deplete cellular antioxidants, such as glutathione, cause mitochondrial damage with prevention of ATP synthesis and induce cell death by lipid peroxidation and DNA fragmentation [50,51,26] . In contrast to our findings, a previous study [1] demonstrated that TiO 2 is physiologically inactive exhibiting relatively low toxicity and considered unhazardous to humans. Many researchers [52][53][54] attributed these results to the very low and poor absorption of TiO 2 NPs after oral administration to rats so it should not result in excessive accumulation of metal in the organism.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…lipid peroxidation), deplete cellular antioxidants, such as glutathione, cause mitochondrial damage with prevention of ATP synthesis and induce cell death by lipid peroxidation and DNA fragmentation [50,51,26] . In contrast to our findings, a previous study [1] demonstrated that TiO 2 is physiologically inactive exhibiting relatively low toxicity and considered unhazardous to humans. Many researchers [52][53][54] attributed these results to the very low and poor absorption of TiO 2 NPs after oral administration to rats so it should not result in excessive accumulation of metal in the organism.…”
Section: Discussioncontrasting
confidence: 99%
“…The aforementioned are consistent with previous researchers who found minimal [22] histological changes on TiO 2 low-dose exposure. Others [1,2] demonstrated that TiO 2 -NPs explicit doseeffect relationship and it does not show any toxicity until the exposure concentration reaches a certain threshold. Many researchers [32,33] revealed that the duration and doses directly determine the results of the biological responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,9,10 Titanium dioxide (TiO 2 ) nanoparticles (nano-TiO 2 ), one of the most widely used form of nanoparticles (NPs) in the world, are extensively used in various areas, including chemical, electronic and solar energy industries, the biomedical fields, and consumer products. 11,12 According to reports in the Project on Emerging Nanotechnologies, nano-TiO 2 are listed within the Top 3 nanomaterials-based consumer products. 13 World production of nano-TiO 2 in 2014 exceeded 9 million metric tons.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the highly diverse nature and characteristics of NPs , their associated toxicological and biological effects are related to exposure pathways, the way they are transmitted to the body and the body's response to them [5,23] (Figure 2). Figure 2: Nanoparticles, depending on their synthesis, can enter the body through different pathways, including inhalation, skin, and digestion.…”
Section: How Do Nps Affect Human Body?mentioning
confidence: 99%